Algorithmic trading engines versus human traders: Do they behave different in securities markets? - Peter Gomber; Markus Gsell (Goethe University Frankfurt, Center for Financial Studies (CFS), 2009)
After exchanges and alternative trading venues have introduced electronic execution mechanisms worldwide, the focus of the securities trading industry shifted to the use of fully electronic trading engines by banks, brokers and their institutional customers. These Algorithmic Trading engines enable order submissions without human intervention based on quantitative models applying historical and real-time market data. Although there is a widespread discussion on the pros and cons of Algorithmic Trading and on its impact on market volatility and market quality, little is known on how algorithms actually place their orders in the market and whether and in which respect this differs form other order submissions. Based on a dataset that for the first time includes a specific flag to enable the identification of orders submitted by Algorithmic Trading engines, the paper investigates the extent of Algorithmic Trading activity and specifically their order placement strategies in comparison to human traders in the Xetra trading system. It is shown that Algorithmic Trading has become a relevant part of overall market activity and that Algorithmic Trading engines fundamentally differ from human traders in their order submission, modification and deletion behavior as they exploit real-time market data and latest market movements.
urn:nbn:de:hebis:30-63808
Keywords: D0; 330; Electronic Markets; Algorithmic Trading; Order Submission; Securities Trading; Wertpapierhandel; Elektronisches Handelssystem; Börsenmakler; Vergleich; Auftragsabwicklung; Deutschland